Stochastic Reactive Distributed Robotic Systems Design, Modeling and Optimization - Mermoud, Gregory; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This monograph presents the development of novel model-based methodologies for engineering self-organized and self-assembled systems. The work bridges the gap between statistical mechanics and control theory by tackling a number of challenges for a class of distributed systems involving a specific type of constitutive components, namely referred to as Smart Minimal Particles. The results described in the volume are expected to lead to more robust, dependable, and inexpensive distributed systems such as those endowed with complex and advanced sensing, actuation, computation, and communication capabilities.
Part I Preliminaries -- Part II Modeling -- Part III Design and Optimization.
Keywords: Engineering; Artificial intelligence; Engineering; Robotics and Automation; Artificial Intelligence (incl. Robotics).